2020
DOI: 10.3390/su12187500
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Assignment of Loading Bays for Efficient Vehicle Routing in Urban Last Mile Delivery

Abstract: Urban freight deliveries are often subject to many access restrictions which creates the need to establish a system of loading bays and to split the last mile delivery into driving and walking parts. A new model based on hard and soft clustering approach is developed to solve the loading bay assignment problem for efficient vehicle routing and walking in last mile delivery. The flexibility of the model is provided by the soft clustering approach based on different membership degrees of customers to loading bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This leads to an increase in the number of commercial tours and low load factor of freight vehicles. Several studies pointed out the high contribution to unsustainability given by goods movements and logistics (Letnik et al [38]; Russo and Comi [46]; and references quoted therein). Besides, the simulation showed that the current delivery bay locations is not optimal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to an increase in the number of commercial tours and low load factor of freight vehicles. Several studies pointed out the high contribution to unsustainability given by goods movements and logistics (Letnik et al [38]; Russo and Comi [46]; and references quoted therein). Besides, the simulation showed that the current delivery bay locations is not optimal.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship, researched by Wenneman et al [50], between delivery bay demand, delivery bay supply, and the number of freight vehicles that park illegally. One of the problems related to delivery bays in cities is that, in many cases, parking supply is lower than demand by carriers (CERTU [10]; Alho and e Silva [2]; De Oliveira and Guerra [24]; Letnik et al [38]). In consequence, freight vehicles double-park along the street or at intersections to load and unload (Ezquerro et al [30]).…”
Section: The Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Loading bays are sometimes occupied, requiring rerouting delivery vehicles and searching for an alternative loading bay. The authors in [78] introduced a fuzzy clustering method to test different optimization approaches and make the system flexible enough to accommodate this problem. We believe that edge AI and computer vision can help address where and how many loading bays should be used to perform this transshipment and execute last-mile delivery most efficiently.…”
Section: Edge Ai For Traffic Monitoring and Managementmentioning
confidence: 99%
“…The upsurge of new technologies eases the process of re-thinking curbs and their dynamic management ( 6 ). Some cities have already experienced progress in implementing Loading Zones (LZ) technology ( 7 ). For instance, city authorities installed parking meters and loop vehicle detection sensors on the LZ floor in Lisbon (Portugal).…”
mentioning
confidence: 99%